LETTERS TO THE EDITOR. - Nollet, Anthony R.; Ramge, Sebastian V.; Evans, Mary Ellen; Mc Cawley, James; Hores, Gabriel F.; Reinhart, Thelma; Darst, David; Libersat Jr., Henry P. (America Magazine: The Jesuit Review of Faith & Culture, 1968)
Several letters to the editor are presented in response to articles published in previous issues including "Financing Catholic Education," by Russell Shaw in the September 28, 1968 issue, "Plight of the Christian," in the October 26, 1968 issue, and "The Unforeseeable Decade," in the October 12, 1968 issue.